Architecture in wood a world history - Pryce, Will (Thames & Hudson, 2016)
Wood has unique qualities, yet is undervalued or ignored in histories of architecture. However, leading designers around the world are increasingly drawn to it to satisfy social and environmental needs. Will Pryce, the most admired architectural photographer in Britain, has travelled the world seeking both famous and obscure buildings in wood. Intensely dramatic but not over-dramatized, technically flawless, but not merely documentary, his photographs convey all the excitement of encountering these amazing structures first hand. In the substantial text he shows how the wooden heritage of Japan grew from its Buddhist history; how Russia's carpenters determined its iconic domes; how Norway's stave churches contain clues to her pagan past; how Turkic tribes brought the yali from Asia; how the settlers of New England would use a provincial English tradition on the new continent; and how, today, sophisticated architects such as Peter Zumthor and Renzo Piano are inventing an eloquent new wooden architecture